A spectrum of non-spore-forming fermentative and non-fermentative Gram-negative bacteria: multi-drug resistance, extended-spectrum beta-lactamase, and carbapenemase production - Desalegn, Yasin; Bitew, Adane; Adane, Amanuel (Frontiers in Antibiotics, 2023)
Background. In developing countries, the co-existence of a high burden of infectious diseases caused by Gram-negative bacteria and the rapid increase and spread of multidrug-resistant bacteria have become a serious health threat. Objective: Profiling of Gram-negative bacteria and determining the magnitude of their antimicrobial resistance among patients. Results: A total of 175 non-spore-forming Gram-negative bacteria were isolated from 873 different clinical samples. Of a total of 175 bacteria, 154 (88%) were fermentative Gram-negative bacteria, while 21 (12%) were non-fermentative Gram-negative bacteria. E. coli with a frequency of 58.3% and K. pneumoniae with a frequency of 18.3% were the predominant fermentative Gram-negative bacteria, while P. aeruginosa 9 (5.1%) and A. baumannii 6 (3.4%) were the predominant non-fermentative Gram-negative bacteria. The highest percentage level of antibiotic resistance was seen against ampicillin (86%), followed by cephalothin (73.2%), trimethoprim/sulfamethoxazole (68.9%), cefazoline (67.1%), and tetracycline (66.5%), whereas the lowest percentage level of resistance was recorded against meropenem (9.8%), tobramycin (18.9%), and nitrofurantoin (19.5%). About 49 (28%) Gram-negative bacilli were positive for ESBLase, out of which the highest percentage was recorded among K. pneumoniae (50%). The overall prevalence rate of MDR bacteria was 80.5%, of which 100% of A. baumannii, 90.6% of K. pneumoniae, 81.4% of E. coli, and 33.3% of P. aeruginosa were MDR. Sixteen isolates were resistant to meropenem, out of which 11 tested for carbapenemase production. Five of the nine were metallo-β-lactamase producers, with the remaining four being serine carbapenemase producers. Conclusion. The prevalence of Gram-negative bacterial infection was found to be 20%, with a significant proportion (80.0%) due to fermentative Gram-negative bacteria and the remaining 20% due to non-fermentative Gram-negative bacteria. The study has also demonstrated a high prevalence rate of MDR, ESBLase, and carbapenemase-producing Gram-negative bacteria. Antimicrobial resistance of Gram-negative bacteria should be monitored on a regular basis, and an effective infection control program should be implemented.